Prevalence of occupational exposure to carcinogens among workers of Arabic, Chinese and Vietnamese ancestry in Australia. Issue 9 (19th June 2015) - Boyle, Terry; Carey, Renee N.; Glass, Deborah C.; Peters, Susan; Fritschi, Lin; Reid, Alison
<x xml:space="preserve">Abstract</x> Background Although job‐related diseases result in more deaths per year than job‐related injuries, most research concerning ethnic minority workers has concerned accidents and injuries rather than disease‐causing exposures such as carcinogens. Methods We conducted a telephone‐based cross‐sectional survey to estimate the prevalence of occupational exposure to carcinogens among a sample of ethnic minority workers in Australia, and compared their exposure prevalence to that of a sample of the general Australian‐born working population ('Australian workers'). Results One‐third of the ethnic minority workers were exposed to at least one carcinogen at work. The likelihood of exposure to carcinogens was not significantly different from that of Australian workers, although the likelihood of exposure to individual carcinogens varied by ethnicity. Conclusion Knowing the prevalence of exposure to carcinogens in the workplace in different ethnic groups will allow better targeted and informed occupational health and safety measures to be implemented where necessary. Am. J. Ind. Med. 58:923–932, 2015. © 2015 Wiley Periodicals, Inc.